Parkraumpolitik und -bewirtschaftung in den Niederlanden. Ausschließlich bargeldloses Zahlen der Parkgebühren im öffentlichen Straßenraum. - Schäfer, Petra K.; Trausch, Zoé (Deutscher Verkehrs-Verl., 2007)
In den Niederlanden ist seit dem 1. Januar 2002 das ausschließlich bargeldlose Zahlen der Parkgebühren im öffentlichen Straßenraum und in Parkhäusern, die von der Stadt betrieben werden, möglich. Die Städte Nijmegen, Purmerend und Rotterdam haben diese Möglichkeit der Bewirtschaftung direkt nach dem gesetzlichen Beschluss eingeführt. Der Artikel beschreibt das ausschließlich bargeldlose Zahlen der Parkgebühren sowie die Erfahrungen, die Kommunen damit gemacht haben. difu

Across the Netherlands, there is great demand for car parking space since the areas currently available have almost reached their limit. For this reason, most cities in the Netherlands have adopted stringent policies concerning car parking. The intention is to relocate cars, which need to be parked long-term, to multi-storey car parks, and to offer the space thus becoming available to local residents and for shod-term parking. This is to be facilitated by the law modified at the beginning of 2002, which also allows local councils to collect parking charges by way of cashless payment methods. Three local councils have differing experiences with this method. In Nijmegen, the introduction of the new payment method promptly caused problems with the automatic car park ticketing machines whereas the cities of Purmerend and Rotterdam have reported positive results. It has been noted that cars formerly parked along main roads, now tend to be parked in multi-storey garages. Vandalism of automatic ticketing machines in car parks has decreased, and there is evidence of drivers' acceptance of other-than-cash payment methods for parking charges. difu
Keywords: Individualverkehr; Parken; Parkhaus; Bewirtschaftung; Öffentlicher Raum; Straßenraum; Gebühr; Verkehrspolitik; Parkraumbewirtschaftung; Parkgebühr; Bargeldlosigkeit; Akzeptanz